Producción de un vídeo promocional para fomentar el sentido de pertenencia del público interno de comunicación social de la Utmach - Suárez Suárez, Ángel Camilo (2016)
The present titling work is focused in the strengthening of the sense of belonging of the students of the Career of Social Communication of the Technical University of Machala, through the production of a promotional video that helps to motivate and despair in the internal public the pride of Belong to this career and the University, working to achieve accreditation. This is why a review, adjustment and complementation of the theoretical information system has been carried out, in order to improve the understanding of the research problem. In addition, the research instruments were established with the aim of having a characterization of the research units by obtaining the information required to achieve the objectives foreseen in the research. For the development of the titling project, techniques were used Interviews and interviews directed to the internal publics, through the design of the questionnaire and the format for the interview, which agrees with the pertinent questions with the subject, formulated grammatically and ordered in a logical way. Among the results that the diagnosis revealed that 50% of the population surveyed students